Comparing estrogen-based hormonal contraceptives and hormone therapy on bone mineral density in women with premature ovarian insufficiency: a systematic review. Issue 3 (March 2022) - Fine, Alexa; Busza, Alicja; Allen, Lisa M.; Kelly, Catherine; Wolfman, Wendy; Jacobson, Michelle; Lega, Iliana C.
Abstract: Importance: Premature ovarian insufficiency (POI) is a condition associated with estrogen deficiency which leads to decreased bone mineral density and an increased risk of osteoporosis and fractures. Estrogen-based hormone therapy is an integral component of treatment; however, to date the ideal hormone formulation for optimizing bone health has not been established. Objective: To assess the effects of estrogen-based oral contraceptives (OCP) versus hormone therapy (HT) on bone mineral density (BMD) in women with POI. Evidence Review: A systematic review of Ovid MEDLINE, EMBASE, Cochrane Library, and Web of Science databases was conducted from conception until December 2020. Randomized controlled trials (RCTs) and observational studies that met inclusion criteria were included in the analysis. Risk of bias was assessed with the Newcastle-Ottawa Quality Assessment Scale for cohort studies and the Cochrane Risk of Bias for RCTs. The study protocol was registered with the International Prospective Register of Systematic Reviews and adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. Findings: Our search yielded 1, 227 studies; 3 RCTs and 2 observational cohort studies met inclusion criteria and were included in our study. The largest subpopulation was Turner Syndrome ( n  = 625), followed by idiopathic POI ( n  = 146). Of the four studies that assessed changes in BMD, two studies reported a significant increase in lumbar spine BMD with HT compared with OCP (+0.050 g/cm 2, P  < 0.025; +0.019 g/cm 2, P  < 0.01), one study found similar improvement in lumbar spine BMD across treatments (HT −0.003 g/cm 2, P  = 0.824), and one study did not directly compare treatments. Effects on bone turnover markers were inconsistent across three studies that evaluated this outcome. Conclusions and Relevance: This is the first systematic review to include studies that directly compared OCP and HT on bone outcomes in POI. While two studies reported increased lumbar spine BMD with HT, this result was not consistently found across studies. There were important differences in POI etiology, treatment regimens and formulations, and risk of bias was high in many of the studies. These results indicate future, larger-scale trials are needed to further understand the optimal hormone therapy for bone density in POI.